Pasantía En La Alcaldía Municipal De Santa Rosa Del Sur, Bolívar - López Villamil, Monica Janeth (Universidad Antonio Nariño, 2024)
The Mayor's Office of Santa Rosa del Sur was established by the Departmental Assembly of Bolívar in 1984 through Ordinance No. 21, its first mayor, Antonio Burgos Gonzáles was appointed by decree, exercising his mandate from 1984 to 1987, later Luis Gonzalo Ariza was established as mayor by decree with a mandate from 1988 to 1989; Since then, ten mandarins have been elected by popular vote; currently, Mayor Miltón Alexis Olaya Santamaría